Aspirin Dosis Rendah untuk Mencegah Preeklamsia pada Kehamilan - Aulia Berliana (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Background. To date, an effective screening algorithm for the identification of women at risk of developing preeclampsia does not yet exist, so prevention of preeclampsia is an important component of prenatal care. Meanwhile, giving low-dose aspirin to pregnant women is thought to prevent preeclampsia in pregnancy. So the aim of this literature review is to determine the effect of aspirin therapy to prevent preeclampsia in pregnancy. Method. This study is a literature review, with the literature used involving as many as 21 of the results literature. Several studies have shown that the effect of low-dose aspirin therapy can significantly reduce the development of preeclampsia, reduce the incidence of preterm birth and small for gestational age significantly. Conclusion. Treatment with low-dose aspirin in women at high risk for preeclampsia resulted in a lower incidence compared with placebo.